IMMU-25. SEVERE AND MULTIFACETED SYSTEMIC IMMUNOSUPPRESSION CAUSED BY EXPERIMENTAL CANCERS OF THE CENTRAL NERVOUS SYSTEM REQUIRES RELEASE OF NON-STEROID SOLUBLE MEDIATORS. (9th November 2020) - Ayasoufi, Katayoun; Pfaller, Christian; Evgin, Laura; Khadka, Roman; Tritz, Zachariah; Goddery, Emma; Fain, Cori; Yokanovich, Lila; Himes, Benjamin; Jin, Fang; Zheng, Jiaying; Schuelke, Matthew; et al.
Abstract: Immunosuppression of unknown etiology is a hallmark feature of glioblastoma (GBM) and is characterized by decreased CD4 T cell counts and down regulation of MHC class II expression on peripheral blood monocytes in patients. This immunosuppression is a critical barrier to the successful development of immunotherapies for GBM. We recapitulated the immunosuppression observed in GBM patients in the C57BL/6 mouse and investigated the etiology of low CD4 T cell counts. We determined that thymic involution was a hallmark feature of immunosuppression in three distinct models of CNS cancer, including mice harboring GL261 glioma, B16 melanoma, and in a spontaneous model of Diffuse Intrinsic Pontine Glioma (DIPG). In addition to thymic involution, we determined that tumor growth in the brain induced significant splenic involution, reductions in peripheral T cells, reduced MHC class II expression on hematopoietic cells, and a modest increase in bone marrow resident CD4 T cells with a naïve phenotype. Using parabiosis we report that thymic involution, declines in peripheral T cell counts, and reduced MHC class II expression levels were mediated through circulating blood-derived factors. Conversely, T cell sequestration in the bone marrow was not governed through circulating factors. Serum isolated from glioma-bearing mice potently inhibited proliferation and functions of T cells both in vitro and in vivo . Interestingly, the factor responsible for immunosuppression in serum is nonsteroidal and of high molecular weight. Through further analysis of neurological disease models, we determined that the aforementioned immunosuppression was not unique to cancer itself, but rather occurs in response to CNS injury. Noncancerous acute neurological insults also induced significant thymic involution and rendered serum immunosuppressive. Both thymic involution and serum-derived immunosuppression were reversible upon clearance of brain insults. These findings demonstrate that CNS cancers cause multifaceted immunosuppression and pinpoint circulating factors as a target of intervention to restore immunity.